FEATURES OF THE USE OF INFORMATIVE RESOURCE ARE IN UKRAINIAN ELECTORAL PRACTICE - Станкевич, Б.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article the question of the use of informative resource is considered during the leadthrough of hustings in Ukraine. Advantages and lacks of basic varieties of informative resource are considered during elektoral'nikh campaigns in domestic practice.  Grounded, that without effective activity of mass medias, the political system does not can it began to develop, after the exception of the totalitarian systems. Key recommendations are formulated in relation to the improvement of possibilities of participation and terms of the use of informative resource in an electoral process.